2002
DOI: 10.11150/kansenshogakuzasshi1970.76.963
|View full text |Cite
|
Sign up to set email alerts
|

Human Parvovirus B19 Infection which First Presented with Petechial Hemorrhage, Followed by Papular-Purpuric Gloves and Socks Syndrome and Erythema Infectiosum

Abstract: A case of human parvovirus B19 (B19) infection is reported. A 6-year-old previously healthy girl was admitted to our hospital complaining of slight fever and petechial hemorrhage on her neck, trunk and the proximal parts of extremities. On admission, the platelet count was within normal range (180 x 10(3)/microliter) but white blood cells and reticulocytes were moderately suppressed (2.4 x 10(3)/microliter and 1@1000, respectively). The purpura disappeared in a week and the blood cell counts fully recovered wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…21 Although erythema infectiosum did develop in 2 of our case patients, this occurred long after disappearance of their petechial rashes. This sequence-petechial rash followed by erythema infectiosum-has been previously described 3,6 and further distinguishes petechial rash in our patients from erythema infectiosum.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…21 Although erythema infectiosum did develop in 2 of our case patients, this occurred long after disappearance of their petechial rashes. This sequence-petechial rash followed by erythema infectiosum-has been previously described 3,6 and further distinguishes petechial rash in our patients from erythema infectiosum.…”
Section: Discussionmentioning
confidence: 61%
“…Petechiae rashes in some of our cases had focal accentuation (in the distal extremities, groin, or axillae), but petechiae were widely distributed in all cases and, in this respect, more closely resembled the generalized rashes described in a few case reports. [1][2][3]10 On the basis of the clinical characteristics of our cases, it seems that parvovirus-associated petechial rash is closely linked to the viremic phase of parvovirus infection. Our case patients typically had fever, systemic symptoms, leukopenia (and occasional thrombocytopenia), and detectable parvovirus DNA in their blood, and acutephase serum tests indicated that a specific antibody response had either not yet developed (IgM-negative) or was just developing (IgM-positive/IgGnegative).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations